2009
DOI: 10.3109/10242420903408211
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of starch granule biogenesis – the role of redox-regulated enzymes and low-affinity carbohydrate-binding modules

Abstract: The deposition and degradation of starch in plants is subject to extensive post-translational regulation. To permit degradation of B-type crystallites present in tuberous and leaf starch these starch types are phosphorylated by glucan, water dikinase (GWD). At the level of post-translational redox regulation, ADPglucose pyrophosphorylase, b-amylase (BAM1), limit dextrinase (LD), the starch phosphorylator GWD and the glucan phosphatase dual-specifi city phosphatase 4 (DSP4), also named starch excess 4 (SEX4), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 49 publications
2
11
0
Order By: Relevance
“…According to recent findings of Glaring et al (2011), CBM45 domain binds to starch and soluble cyclodextrin with about twice lower affinity than classical microbial SBDs, such as CBM20 or CBM21. Such findings support the previous hypothesis that low-affinity SBDs are important for dynamic and reversible interactions in starch metabolism (Blennow and Svensson 2010). This has been confirmed by relation between obtained docking scores for CBM45 and CBM20 models.…”
Section: Molecular Mass Determinationsupporting
confidence: 90%
See 1 more Smart Citation
“…According to recent findings of Glaring et al (2011), CBM45 domain binds to starch and soluble cyclodextrin with about twice lower affinity than classical microbial SBDs, such as CBM20 or CBM21. Such findings support the previous hypothesis that low-affinity SBDs are important for dynamic and reversible interactions in starch metabolism (Blennow and Svensson 2010). This has been confirmed by relation between obtained docking scores for CBM45 and CBM20 models.…”
Section: Molecular Mass Determinationsupporting
confidence: 90%
“…in starch degradation. Of note, the final activity of individual proteins may be the result of post-translational modifications, such as proteolytic modifications, changes in redox potential or phosphorylation/dephosphorylation (Smith et al 2005;Orzechowski 2008;Blennow and Svensson 2010). In Arabidopsis leaves, the phosphatase SEX4 (Hejazi et al 2010) was detected, which acts in opposition to glucan, water dikinases.…”
Section: Changes In Stgwd3 Expressionmentioning
confidence: 99%
“…The very closely positioned C-3 and C-6 phosphorylated glucose residues found in hydrolysates of potato starch (Kamasaka et al 1997b) indicate the in vivo action of PWD/GWD3 as well as the requirement for closely situated phosphate groups in the substrate glucan. Of specific interest is that CBM45 and CBM20 found in plants have lower affinity (mM) towards starch than typical microbial CBMs (M) Blennow and Svensson 2010;Glaring et al 2011). Such differences in substrate specificity between GWD and PWD/GWD3 create metabolic dependence between these two activities in the plant cell that is potentially important for the physiological effect of starch phosphorylation.…”
Section: Discovery Of Pwd/gwd3mentioning
confidence: 99%
“…However, it was later demonstrated that also non-phosphorylated chains could be phosphorylated provided that these were co-crystallised with phosphoglucans ). In contrast to the high affinity of the extracellular CBMs, the low affinity found for these intracellular and plastidial CBMs would ensure dynamic and reversible interactions between the enzymes and starch granule in starch phosphorylation at different light regimes and at stress situations Blennow and Svensson 2010;Glaring et al 2011). This is further described in Sect.…”
Section: Discovery Of Pwd/gwd3mentioning
confidence: 99%
“…This step is the cleavage of -1,6 linkages by isoamylase-type DBE [10,41]. The DBE are crucial for the generation of longer, clustered linear segments in the amylopectin molecule that can crystallize and increase the density of the polysaccharide [42]. Plants contain four DBE genes, three of which are classified as isoamylases on the basis of their sequence homologies and substrate specificities, and one pullulanase-type debranching enzyme [10,43].…”
Section: Overview Of the Starch Biosynthesis And Degradation In Plantsmentioning
confidence: 99%